Active tuberculosis identification based on workers environmental sanitation during the COVID-19 pandemic - Tri Hari Irfani; Agita Diora Fitri; Eddy Roflin; Reynold Siburian; Tungki Pratama Umar (Public Health of Indonesia)
Background: Coronavirus Disease 2019 (COVID-19) is a pandemic that may complicate the active detection of Tuberculosis (TB) and increase the mortality rate. This pushes for more effective and efficient case finding to mitigate the possible growing number of TB mortality.